The English Language Drama In Malaysia A Study Of It's Developments, Themes And Styles - Chee, Moon Leng (Pusat Pengajian Ilmu Kemanusiaan, 1982)
Malaysian English drama is relatively new in this country, having really gathered impetus only in the 1960s onwords or to that, the only drama which existed apart from traditional form was the Bangsawan, a popular transitional theatre of the late 19th century. Amateur production of Western plays no doubt went on among the British who had, beginning from the late 18th century, colonized parts of the Malat peninsular.